2019
DOI: 10.1002/jpln.201900038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urease and nitrification inhibitors on ammonia volatilization and abundance of N‐cycling genes in an agricultural soil

Abstract: The effect of the combined application of urease and nitrification inhibitors on ammonia volatilization and the abundance of nitrifier and denitrifier communities is largely unknown. Here, in a mesocosm experiment, ammonia volatilization was monitored in an agricultural soil treated with urea and either or both of the urease inhibitor N-(n-butyl) thiophosphoric triamide (NBPT) and the nitrification inhibitor 3,4-dimethylpyrazole phosphate (DMPP), with 50% and 80% water-filled pore space (WFPS). The effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…Specifically, the AOB population exhibits a strong response to N fertilizers [48]. Shortly after the fertilizer application, soils tend to show a large increase in amoA abundance [39,49]. This growth can be avoided by applying SNIs such as DMPP, and the AOB population size is maintained at the level of unfertilized soils (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the AOB population exhibits a strong response to N fertilizers [48]. Shortly after the fertilizer application, soils tend to show a large increase in amoA abundance [39,49]. This growth can be avoided by applying SNIs such as DMPP, and the AOB population size is maintained at the level of unfertilized soils (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4.21c and d). This result is the opposite to that of Castellano-Hinojosa et al (2019a), who suggested that the UI did not affect the copy number of the nosZ gene at 50% WFPS, but is in agreement with Shi et al (2017), who have observed a decrease in the abundance of nirK genes below a WFPS of 60%.…”
Section: Processes Involve In the N2o Productionsupporting
confidence: 72%
“…To some extent, UI retarded the urea hydrolysis by decreasing urease activity and so slowed the conversion of urea-N to , which led to a slow-down in the reduction of to [ 37 , 38 ]. In our study, 80%U+UI decreased the urease activity between 15 and 45 DAF and decreased the nitrate reductase activity between 5 and 30 DAF ( Fig 2 ).…”
Section: Discussionmentioning
confidence: 99%